2008
DOI: 10.1089/rej.2007.0583
|View full text |Cite
|
Sign up to set email alerts
|

Hypermagnesemia Predicts Mortality in Elderly with Congestive Heart Disease: Relationship with Laxative and Antacid Use

Abstract: The aim of this study was to evaluate the role of magnesium levels on 3-year survival in the elderly with congestive heart failure (CHF) admitted to the Rehabilitative Cardiology Unit of S. Maugeri Foundation Scientific Institute of Telese/Campoli. All elderly patients > or = 65 years old with a diagnosis of CHF underwent clinical and instrumental examination, and their demographics, co-morbidity, and in-hospital and 3-year mortality rates were recorded. Hypomagnesemia was found in 4.8%, normomagnesemia in 67.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
28
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 42 publications
(34 reference statements)
0
28
0
Order By: Relevance
“…5 In another study of patients admitted to an Italian rehabilitation unit, hypermagnesemia was associated with increased risk of mortality at 3-year follow-up. 6 These studies have been small single-center experiences with limited covariate adjustment, likely explaining the observed discrepancies in findings from the present investigation.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…5 In another study of patients admitted to an Italian rehabilitation unit, hypermagnesemia was associated with increased risk of mortality at 3-year follow-up. 6 These studies have been small single-center experiences with limited covariate adjustment, likely explaining the observed discrepancies in findings from the present investigation.…”
Section: Discussionmentioning
confidence: 57%
“…5 An Italian study with follow-up up to 3 years showed that hypermagnesemia was associated with increased mortality in elderly patients with HF. 6 These incongruent data highlight the need for more robust and complete characterization of the clinical profiles and prognostic impact of serum magnesium levels during hospitalization for HF. The Efficacy of Vasopressin Antagonism in Heart Failure Outcome Study with Tolvaptan (EVEREST) 7,8,9 dataset provides insight into the longitudinal electrolyte profiles in a large cohort of hospitalized patients with HF.…”
mentioning
confidence: 99%
“…The significant elevations in serum magnesium levels, and the possibility of increased phosphate levels, might be the result of osmotic diuresis caused by SGLT2 inhibitors, but the precise mechanisms involved are unknown. Abnormally high magnesium levels are predictive of total mortality in individuals with heart failure [22], those who are critically ill [23] and those receiving haemodialysis [24]. Therefore, caution must be exercised in patients with impaired renal function, such as in severe CKD.…”
Section: Discussionmentioning
confidence: 99%
“…Magnesium is one of several nutrients that may cause detrimental effects when present in excess, such as neuromuscular effects (confusion, lethargy, respiratory depression, muscle weakness/paralysis), cardio vascular effects (hypotension, bradycardia, cardiac arrest) and nausea and vomiting (3,5).…”
Section: D1scuss]onmentioning
confidence: 99%